1989
DOI: 10.1182/blood.v73.5.1195.1195
|View full text |Cite
|
Sign up to set email alerts
|

Combined and sequential effects of human IL-3 and GM-CSF on the proliferation of CD34+ hematopoietic cells from cord blood

Abstract: The proliferative effects of recombinant human interleukin-3 (IL-3) and granulocyte-macrophage colony-stimulating factor (GM-CSF) were investigated in semi-solid and liquid cultures of purified CD34+ hematopoietic cells obtained from umbilical cord blood. No important differences in overall cloning efficiencies in response to IL-3 or GM- CSF were observed in semi-solid medium in the presence of erythropoietin (Ep). However, GM-CSF was less effective for the development of erythroid bursts (BFU-E), and only IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…The higher expression of theTfR (a proliferation marker) on cells from cultures supplemented with GM-CSF is in agreement with these findings and coincides with an increase of progenitors (blasts) in GM-CSF-containing cultures. Furthermore, an increased number of GM-CSF was observed under similar conditions in earlier studies [14].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The higher expression of theTfR (a proliferation marker) on cells from cultures supplemented with GM-CSF is in agreement with these findings and coincides with an increase of progenitors (blasts) in GM-CSF-containing cultures. Furthermore, an increased number of GM-CSF was observed under similar conditions in earlier studies [14].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, GM-CSF seems to promote an expansion of myeloid precursors and of more mature granulocytic cells (CDllc+, CD15+ and CD14-elements). Other authors have described the ability of GM-CSF to induce a generation of myeloid progenitors from CD34+ cells [14].We have shown that this process is connected with a decrease in the number of immature cells due to their maturation into CD34precursors. In agreement with the in vivo effects of GM-CSF, which caused an earlier increase of the number of granulocytes, but only a marginal and delayed production of monocytes [20], the in vitro effect of GM-CSF observed in this study may be due to the preferential stimulation of granulocytic differentiation.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The same effect was observed for multipotent-colony forming units (CFU-GEMM) when SCF was added to interleukin 3 (IL-3) and erythropoietin (EPO). Moreover, on CD34' purified cord blood stem cells, an enhanced proliferation of CFU-GM was obtained in the presence of combinations of IL-3 and GM-CSF [6]. The same stimulatory effect was observed on bone marrow CFU-GM growth when SCF was associated with IL-3 or GM-CSF [7].…”
Section: Introductionmentioning
confidence: 63%
“…2). In this regard, several cytokines (including SCF, interleukin 1 (IL‐1), IL‐3, IL‐6, GM‐CSF, G‐CSF, M‐CSF, erythropoietin (Epo), thrombopoietin (Tpo), and FL have been assessed, either alone or in combination, in cultures of UCB‐derived CD34 + cells [10, 40, 48, 6677]. In terms of HPC expansion, the best results have been obtained when cytokines are used in combinations that include early‐acting factors, such as SCF, FL, and Tpo.…”
Section: In Vitro Characterization Of Ucb Hspcmentioning
confidence: 99%